INNOVATION IN GLOBAL INDUSTRIAL DOWNSTREAMING: AN OVERVIEW LITERATURE ABOUT OPPORTUNITIES, CHALLENGES AND POLICY DIRECTIONS - Aditya Hera Nurmoko; Heru Wahyudi; Tri Suyud Nusanto; Abdi Ramdan; Oki Permata Aji (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Downstream industry has become an important strategy in transforming the global economy, especially in developing countries rich in natural resources Power nature. This article serves as a review of the literature comprehensive to innovation in the downstream global industry with a highlight of forms of innovation, strategic opportunities, challenges, implementation, and policy implications. Through approach analysis thematic against 25 journals relevant of 100 journals indexed by Scopus (2003–2023), this research identify role crucial of innovation technology and digitalization — such as bioprocess, real-time information receiving (RTIR), as well as adoption of Industry 4.0— in increase efficiency and value add in sector downstream. This study also highlights the opportunity integration of bioeconomics and economic circular, and challenges like limitations on infrastructure, cost height, and obstacles to regulation. Implications policy shows the importance of synergy between the regulation industry, the environment, and innovation, as well as the need for support towards MSMEs, R&D, and infrastructure downstream. Study results: This gives a runway conceptual and practical for formulation of downstream strategy based on adaptive innovation to global and local dynamics.